The Spirituality of Black Hebrew Pentecostals - Sherron, Fred G. (UJ Press, 2023)
The spirituality of Black Hebrew Pentecostalism is a rich tradition that has been hidden from the view of scholars. With the new interest in spirituality forming the background to this title, the author attempts to enlighten readers about this tradition.